IMPLEMENT OUTDOOR ACTIVITY TO MULTIPLE INTELLIGENCE’S DEVELOPMENT EARLY AGE AT BATUJAYA’S DISTRICT KARAWANG’S REGENCY - Tedi Purbangkara, Rahmat Iqbal, Azhari Ali Ridha (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research is appointed up on effort and government policy that corresponds to early age child requirement in learning and development self, of science facet (kognitif), attitude (afektif) and power skill (psikomotor). To perform that government policy needs to mark sense research that aims to increase ability, keaktifan and proprietary learning creativity that PAUD’S teacher better again, learning that gets basis Outdoor Activity to development multiple intelligence early age child and to know evaluation implement gets basis multiple intelligence at HIMPAUDI Batujaya Karawang’s regency this Research constitute kualitatif’s descriptive research; its data collecting tech doing to utilize observation method, interview, anecdotal note, and documentation. Result observationaling to point out that PAUD’S learning development gets basis multiple intelligence on early age child at HIMPAUDI Batujaya did by integrates it into learning material that is arranged on curriculum. Besides, learning development outdoor activity to development multiple intelligence done by outboard activity and also at within class with plays role, singing, relate, wisata’s opus involve straightforward child in activity, get discussion, get sport and takes the air. Learning that involves all protege intelligence will impacted positive to the future child.